Effects of Electrode-Tissue Proximity on Cardiac Lesion Formation Using Pulsed Field Ablation. (27th September 2022) - Howard, Brian; Verma, Atul; Tzou, Wendy S.; Mattison, Lars; Kos, Bor; Miklavčič, Damijan; Onal, Birce; Stewart, Mark T.; Sigg, Daniel C.
Abstract : Background: Pulsed field ablation (PFA) is a novel energy modality for treatment of cardiac arrhythmias. The impact of electrode-tissue proximity on lesion formation by PFA has not been conclusively assessed. The objective of this investigation was to evaluate the effects of electrode-tissue proximity on cardiac lesion formation with a biphasic, bipolar PFA system. Methods: PFA was delivered on the ventricular epicardial surface in an isolated porcine heart model (n=8) via a 4-electrode prototype catheter. An offset tool was designed to control the distance between electrodes and target tissue; deliveries were placed 0 mm (0 mm offset), 2 mm (2 mm offset), and 4 mm away from the tissue (4 mm offset). Lesions were assessed using tetrazolium chloride staining. Numerical models for the experimental setup with and without the offset tool validated and supported results. Results: Cardiac lesion dimensions decreased proportional to the distance between epicardial surface and electrodes. Lesion depth averaged 4.3±0.4 mm, 2.7±0.4 mm, and 1.3±0.4 mm for the 0, 2, and 4 mm and lesion width averaged 9.4±1.1 mm, 7.5±0.8 mm and 5.8±1.4 mm for the 0, 2, and 4 mm offset distances, respectively. Numerical modeling matched ex vivo results well and predicted lesion creation with and without the offset tool. Conclusions: Using a biphasic, bipolar PFA system resulted in cardiac lesions even in the 0 mm offset distance case. The relationship between lesion depth and offset distance was linear, and the deepest lesions were created with 0 mm offset distance, that is, with electrodes in contact with tissue. Therefore, close electrode-tissue proximity increases the likelihood of achieving transmural lesions by maximizing the electric field penetration into the target tissue.